Juvenile psoriasis: a case report - S, Ishwarya; R, Revathi Shree; K, Bharathi; Nerune, Savitri M.; D, Manimaran (International Journal of Contemporary Pediatrics, 2017)
Psoriasis is a chronic inflammatory immunologically mediated dermatoses characterized by erythematous plaque covered by loosely adherent scales. Psoriasis in children is a rare entity which may lead to psychological impairment and complications, hence early recognition and management of psoriasis in children is crucial. Here we present a case of 2 year old boy with multiple erythematous scaly plaques over lower back, gluteal region, elbows, knees and lower legs. Biopsy from gluteal region showed microscopic features of psoriasis. This case is presented here to highlight the importance of early recognition and management of juvenile psoriasis.